Making infection prevention and control everyone's business? Hospital staff views on patient involvement. (17th February 2019) - Sutton, Elizabeth; Brewster, Liz; Tarrant, Carolyn
Abstract: Context: Ensuring an infection‐free environment is increasingly seen as requiring the contribution of staff, patients and visitors. There is limited evidence, however, about how staff feel about collaborating with patients and relatives to co‐produce that environment. Aims: This study aims to understand how hospital staff perceive the involvement of patients and relatives in infection prevention and control (IPC) and the main challenges for staff in working together with patients and relatives to reduce the threat of infection. Methods: Qualitative semi‐structured interviews were conducted with 35 frontline health‐care professionals and four executive staff, from two hospital trusts. Findings: We found that staff were more supportive of approaches that encourage co‐operation from patients and relatives, than of interventions that invoked confrontation. We identified challenges to involvement arising from staff concerns about shifting responsibility for IPC onto patients. Staff were not always able to work with patients to control infection risks as some patients themselves created and perpetuated those risks. Conclusions: Our work highlights that IPC has particular features that impact on the possibilities for involving patients and relatives at the point of care. Staff acknowledge tensions between the drive to involve patients and respect their autonomy, and their duty to protect patients from risk of unseen harm. The role that patients and relatives can play in IPC is fluctuating and context dependent. Staff responsibility for protecting patients from the risk of infection may sometimes need to take priority over prerogatives to involve patients and relatives in the co‐production of IPC.